2006
DOI: 10.1002/anie.200502530
|View full text |Cite
|
Sign up to set email alerts
|

Why Are Proteins Charged? Networks of Charge–Charge Interactions in Proteins Measured by Charge Ladders and Capillary Electrophoresis

Abstract: Almost all proteins contain charged amino acids. While the function in catalysis or binding of individual charges in the active site can often be identified, it is less clear how to assign function to charges beyond this region. Are they necessary for solubility? For reasons other than solubility? Can manipulating these charges change the properties of proteins? A combination of capillary electrophoresis (CE) and protein charge ladders makes it possible to study the roles of charged residues on the surface of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
316
1
6

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 256 publications
(334 citation statements)
references
References 249 publications
(292 reference statements)
11
316
1
6
Order By: Relevance
“…Previous studies have attributed the infrequent participation of Lys in interfaces to the entropic cost of restricting its highly mobile side chain. 14,28 This proposal seems to be incompatible with our results (for the specific but very well-defined The results of this study also emphasize the significant role of surface charges in mediating interactions between proteins, 29,30 and suggest that charges, as a constraint in determining proteinprotein interfaces, might be modulated (or reduced) to control biomolecular recognition. We showed that acetylation of positively charged lysine residues gives rise to new protein-protein interfaces, which are less complementary electrostatically but which involve contacts that are more well-defined geometrically.…”
Section: Discussioncontrasting
confidence: 82%
“…Previous studies have attributed the infrequent participation of Lys in interfaces to the entropic cost of restricting its highly mobile side chain. 14,28 This proposal seems to be incompatible with our results (for the specific but very well-defined The results of this study also emphasize the significant role of surface charges in mediating interactions between proteins, 29,30 and suggest that charges, as a constraint in determining proteinprotein interfaces, might be modulated (or reduced) to control biomolecular recognition. We showed that acetylation of positively charged lysine residues gives rise to new protein-protein interfaces, which are less complementary electrostatically but which involve contacts that are more well-defined geometrically.…”
Section: Discussioncontrasting
confidence: 82%
“…The electrophoretic mobility, μ (eq 11), of a molecule is proportional to its charge, Z, and inversely proportional to its molecular weight, M ,395 where the exponent α relates the molecular weight of the protein to its hydrodynamic drag and C P is a proportionality constant. 394,[396][397][398] Equation 11 shows that a change in the electrophoretic mobility of the protein can be altered by a ligand that changes (i) the charge of the receptor, (ii) the hydrodynamic drag of the receptor, or (iii) both. (11) When CA binds to an arylsulfonamide, the change in the hydrodynamic drag of the protein is negligible, and the assay relies on having a charged ligand to produce a significant change in the charge of the protein-ligand aggregate and, thus, a change in the electrophoretic mobility of the receptor ( Figure 9A).…”
Section: Affinity Capillary Electrophoresismentioning
confidence: 99%
“…(12) A Scatchard plot of Δμ P,L /[L] versus Δμ P,L results in a line with slope equal in magnitude to the binding constant, where Δμ P,L is the difference between the mobility of the protein (P) at a given concentration of ligand, [L], and the mobility the protein without the ligand. 394,[396][397][398] Determination of the binding constant of CA to neutral ligands requires a competitive binding assay because small neutral ligands do not cause a shift in the mobility of the protein. The competitive assay involves the addition of a neutral ligand to a sample of CA containing a fixed concentration of a charged ligand of known affinity.…”
Section: Affinity Capillary Electrophoresismentioning
confidence: 99%
See 2 more Smart Citations